Conceptual clarification and practical application on commercial law concepts - Li, Lei (International Journal of Global Economics and Management, 2024)
The concept of commercial law is inseparable from the thinking of commercial law, and the concept of commercial law is the core spirit of the operation of commercial law thinking. Its contents include profit-making thinking, businessmen's autonomy, prioritizing efficiency and guaranteeing safety. Compared with civil law norms, commercial law concept has a comparative advantage for the application of rules of commercial practice, in terms of company law, the establishment of the company and the goodwill of the company is not effectively protected in the traditional civil law. The teaching practice of business law concepts is currently structurally deficient and needs to be optimized in the design of future teaching reforms. At the practical level, the overall work of optimizing the business environment cannot be separated from the support of the rule of law, and the value guidance of the concept of business law is even more indispensable.